Hydrophile-lipophile balance (HLB) of n-alkane phosphonic acids and theirs salts - Verdinelli, Valeria (2008)
As a previous step in their application as emulsifiers, here we performed a study of the hydrophile-lipophile balance (HLB) properties of decyl (C10H21PO3H2), dodecyl (C12H25PO3H2), tridecyl (C13H27PO3H2) phosphonic acids and their mono and disodic salts. Two different methods (Griffin and Greenwald et al. methods) were applied. The HLB values along with the -PO3H2; -PO3HNa and PO3Na2 HLB group numbers found by Greenwald et al. method were comparable to those obtained for similar structure surfactants. The HLB computed by Griffin emulsion technique strongly depends on the nature of the emulsifier mixture compounds, and was shown inappropriate to study this kind of surfactants. This fact is interpreted because of the hydrocarbon/water structure. © 2007 Elsevier B.V. All rights reserved.